Reflexive and Methodological Views on the Role of Artistic Creativity in the System of Personal Artistic Aesthetic Activity - Allayarova Marhabo Mavlonovna (Genius Publishing Group, 2022)
The article is devoted to the interdisciplinary study of modern problems of artistic creativity. Philosophical levels and aspects of the creative process are considered: cognitive, personal-motivational, cultural, and spiritual-systemic. It is also researched that artistic creativity by its nature is a reflexive process and is a phenomenon of spiritual culture. It is analyzed that high works of art are the result of conscious perception by the creator and a corresponding rise in emotions to the level of spiritual experience
Keywords: artistic creativity; culture; spirituality; reflection